Costa Rica : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Costa Rica. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses key issues related to the economy of Costa Rica. It bounced back quickly from the global financial crisis; growth has moderated below trend and macro vulnerabilities, mainly from the weak fiscal position, are rising. Policy actions have been broadly consistent with past IMF advice. A third year of growth below potential has resulted in a moderate output gap. The central bank took advantage of the favorable shock from lower oil prices to reduce its inflation target range. The exchange rate has been stable despite abandonment of band regime, and reserve accumulation has resumed strongly. The external position is close to equilibrium, with competitiveness largely unchanged in 2014-15.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet